Serological risk factors for steroid-induced osteonecrosis in HIV men: a Bayesian case–control study - Ji, Yunxiao; Li, Kangpeng; Zhao, Rugang; Zhao, Changsong; Zhang, Qiang (Frontiers in Medicine, 2025)
BackgroundHuman immunodeficiency virus (HIV)-infected individuals face diagnostic challenges for non-traumatic hormonal necrosis of femoral head (SONFH), as current imaging methods lack sensitivity/specificity and reliable biomarkers remain elusive. While coagulation disorders and dyslipidemia are known risk factors, evidence in HIV populations is limited.MethodsThis case–control study enrolled 48 HIV-positive males with SONFH and 50 controls from Beijing Ditan Hospital (2021–2025). We analyzed demographic, coagulation, inflammatory, and metabolic markers. Random forest selected top 20 predictors, followed by Bayesian regression to assess associations (reported as OR, 95% CI, posterior probabilities, and Bayes factors).ResultsTriglycerides (TG) showed the strongest SONFH association (OR = 85.911, 95% CI: 4.733–3078.857; BF = 82.048). Fibrinogen degradation products (FDP) (OR = 6.968, 95% CI: 1.485–51.347; BF = 6.692) and plasma thromboplastin antecedent (PTA) (OR = 2.890, 95% CI: 1.131–11.146; BF = 2.046) also demonstrated significant risk associations. Prolonged prothrombin time (PT) was protective (OR = 0.008, 95% CI: 0.0002–0.234; BF = 37.897).ConclusionElevated triglycerides, FDP, and PTA significantly increase the risk of SONFH in HIV patients, while prolonged PT may be protective. These serum markers could guide early intervention, though larger prospective studies are needed.